1994
DOI: 10.1177/000348949410301012
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Oxygen Metabolite Inhibition of Cultured Chinchilla Middle Ear Epithelial Cell Growth

Abstract: Middle ear inflammation in acute bacterial otitis media is characterized by accumulation of neutrophils in middle ear effusion. Since neutrophils release products that may injure surrounding tissues, we studied the effect of neutrophil metabolic products on middle ear epithelial cells (MEECs) in vitro. Chinchilla MEECs were incubated with phorbol myristate acetate (PMA)-activated human neutrophils or with hydrogen peroxide (H2O2). Cell growth, which was measured by 3H-thymidine incorporation, was inhibited by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Neutrophils release free radicals such as H202, which may inhibit the cell nietabolism and thus prolong the niiddle ear inflammatory response and lead to chronic tissue damage. The effect of neutrophil metabolic products on middle ear epithelial cells of the chinchilla was studied in vitro by Kawana et al [20]. They demonstrated that cell growth was inhibited by activated neutrophils whereas tinstimulated neutrophils did not affect the viability of these cells.…”
Section: Effusionmentioning
confidence: 99%
“…Neutrophils release free radicals such as H202, which may inhibit the cell nietabolism and thus prolong the niiddle ear inflammatory response and lead to chronic tissue damage. The effect of neutrophil metabolic products on middle ear epithelial cells of the chinchilla was studied in vitro by Kawana et al [20]. They demonstrated that cell growth was inhibited by activated neutrophils whereas tinstimulated neutrophils did not affect the viability of these cells.…”
Section: Effusionmentioning
confidence: 99%